At Face Value and Beyond Photographic Constructions of Reality - Schwärzler, Monika (Image, 2016)
How to account for the peculiar attraction of certain photos? How to deal with the specific use of images in particular contexts? Monika Schwärzler presents a variety of photographic case studies exploring visual phenomena from the point of view of media analysis as well as from sociological, aesthetic, and psychoanalytic perspectives. The topics range from a new reading of Thomas Struth's street photographs to CERN photos with their charged rhetoric, from the assault of photographic close-ups to speculations on an anonymous slide collection featuring a woman with an ever-present white handbag. The book is intended for an audience receptive to the analytical appeal of images, prepared to go beyond what can be taken at face value.